Giant ovarian tumors: diagnosis, management, and treatment: Tumores ováricos gigantes: diagnóstico, manejo y tratamiento - Briceño-Pérez, Carlos; Castro, Bairon; Hurtado, Oscar; Ríos, Rosa; Study Group, the GOT (Gaceta Médica de Caracas, 2026)
The large size of some tumors has been described with fascination over time. These include gynecological ones, of which cases of enormous growth are described, especially before the advent of ultrasound. The terminology used to describe these large tumors contains a variety of confusing qualifiers, including “immense”, “extensive”, “voluminous”, “massive”, “large”, “very large”, “giant”, and “ gigantic gigantic”. Likewise, their measurements are usually used to refer to “giants”, but the limits for their definition are not mentioned. In the English literature, there has been agreement for 54 years on defining uterine or ovarian tumors weighing more than 25 lb. as “giants”, because, in 1971, the uterine or ovarian tumors, between 1946-1970, weighing 25 lb. or more, were reviewed.